CZY JESTEŚMY GOTOWI NA EKOGLOTTODYDAKTYKĘ W POLSKIM KONTEKŚCIE EDUKACYJNYM? - Sujecka-Zając, Jolanta (Neofilolog, 2020)
The trend for eco-linguistics, which has been dynamically developing in the English-language literature since the 1970s, proposes a change in the perception of the relationship between language, nature, and culture, in a sense making language a link which brings together nature and culture, rather than separating them as is traditional. This approach poses important questions: How do languages ​​work in the ecosystem created by the language environment of all users of a given language context? What relationships can they enter into? How should one perceive the development of multilingualism in such an ecological approach, in which not only does "strong" affect the "weak" but “weak” reciprocates? "Weak" has an important place in the language ecosystem, which risks serious changes due to excessive weakening of one of its components. This paper aims to examine the possible inspirations that eco-linguistics offers Foreign Language Teaching (FLT), highlighting the role of each language and sensitizing the reader to the relationships that arise between languages ​​and their users in a given environment. From this perspective Claire Kramsch (2008) postulates a change in the perception of the main function of the teacher from the "teacher of a code" to the "teacher of meaning", which has specific didactic consequences in how language activities are approached. Is the school classroom a place for activities which have their origin in the trend for eco-FLT?